Studies on the Vorticity of Superconducting 3D Nano-Sized Pyramidal Samples as a Function of the Coherence Length (Journal of Bangladesh Academy of Sciences, 2025)
This study examines the vorticity of a nano-sized superconducting pyramidal sample using the 3D Ginzburg-Landau (GL) formalism, a crucial tool for analyzing the nonuniform geometrical sample. We consider a field applied perpendicularly to the base of the pyramid and characterize static properties of the sample as a function of its coherence lengths. The study focuses on the nucleation point of the vortex (vortex penetration field) and the vortex configuration within the sample. We measure the free energy and magnetization of the sample with the applied magnetic field increases and observe steady properties on the plane orthogonal to the field. We examine two samples with different coherence lengths, one having a coherence length of 12ξ and the other 6ξ. The study investigates the variation of the stability range of the Meissner state and the critical field of the pyramidal sample as a function of the coherence length.J. Bangladesh Acad. Sci. 49(1); 35-44: June 2025